Improving knowledge, attitudes, and practices of COVID-19 reduction through Santri Husada Program - Ikhsan, M. Alifudin; Faris Khoirul Anam; Yusuf Hanafi; Abdul Adzim; Zahrotul Muzdalifah (Journal of Community Service and Empowerment, 2021)
Prefentive and currative efforts of COVID-19 in pesantren is a crucial points to be done in order to conduct conducive and safe learning situation. This community service aims to form, train and assist Santri Husada in carrying out its role in the health sector of Islamic boarding schools. This campus environmental service program offers many paradigm shifts for students by allowing them to participate in maintaining the health of pesantren residents who have previously appeared to disregard health protocols. It was carried out in three phases, namely education and outreach, training, and intensive mentoring from March to May 2021 at Darul Faqih Islamic Boarding School Malang. The survey results on students’ knowledge, attitudes and practices towards COVID-19 showed a good score with the correlation (R-square: P-Value) knowledge-attitude (0.167: 0.000), knowledge-practice (0.060: 0.000) and attitude-practice ( 0.051: 0.000). This community service program was carried out in collaboration with LP2M Universitas Negeri Malang, UPT Wagir Health Center, Polyclinic of Universitas Negeri Malang and the COVID-19 Task Force, Wagir District, Malang Regency. The Santri Husada Program has made a real contribution in suppressing the spread of COVID-19 in the Islamic boarding school environment and led it a tough Islamic boarding school area.